Kinerja Dosen terhadap Proses Pembelajaran di Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci - Saaduddin Saaduddin (Journal on Education, 2022)
Along with the rapid development of the times, at the same time the construction industry has also grown rapidly. Along with the development of that era, the technology and construction methods in the world are increasingly developing. This also applies in Indonesia, construction methods in Indonesia are also developing. One form of the development of construction methods in Indonesia is the precast construction method. This study aims to determine how much the costs and how long it takes to implement the Cast In Situ and Precast Methods of columns and beams.The method used in this research is a quantitative method using the calculation of SNI 7394: 2008 "concerning the procedure for calculating the unit price of concrete work for building and housing construction" and SNI 7832 - 2012 "concerning the procedure for calculating the unit price of precast concrete work for building construction. building".From the research results, it is found that the overall budget plan for the application of column and beam structures using conventional concrete methods is Rp. 973,127,521.20. And the overall budget plan for the application of column and beam structures using the Precast concrete method is Rp. 1,317,764,550. From the calculation results, it was found that the analysis of the duration of working on the column and beam structures on floors 1-3 with the conventional concrete method was 223 days, while for the analysis of the duration of working on the column and beam structure with the precast concrete method was 202 days. In this study, it can be concluded that the difference in price between the conventional concrete method and precast concrete is IDR 344,637,029.27 or the precast concrete method is 26% more expensive than the conventional concrete method, with a difference in processing time of 21 days, or implementation The precast method is 21 days faster than the conventional concrete method.